2008
DOI: 10.1111/j.1570-7458.2008.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring virulence in Asian rice gall midge populations in India

Abstract: The Asian rice gall midge, Orseolia oryzae (Wood‐Mason) (Diptera: Cecidomyiidae), is a major pest of rice [Oryza sativa L. (Poaceae)] in India. Breeding resistant varieties and their cultivation has been the main approach to manage this pest. However, the breakdown of resistance conferred by the major genes, deployed one at a time, through evolution of virulent biotypes has become a major setback to this approach. Development of polymerase chain reaction‐based molecular markers for eight of the 10 resistance g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…Most of but not all, R-gene-triggered resistance is accompanied with HR. Insect resistance with HR-like symptoms have also been observed in cases such as wheat (Triticum aestivum) Grover 1995), peach (Prunus persica) resistance to the aphid Myzus persicae (Sauge et al 1998), rice (O. sativa) against the gall midge O. oryzae (Bentur et al 2003), willow (Salix viminalis) tree varieties against the gall midge (Dasineura marginemtorquens; Hoglund et al 2005) and bean (Phaseolus vulgaris) resistance to the bean-pod weevil (Apion godmani; Garza et al 2001). Cell death that occurs during HR+ type resistance is reported to be controlled by the oxidative burst (Atkinson et al 1996;Heath 2000), production of NO (Delledonne et al 2002), and the interaction between some of these different signaling pathways (Delledonne et al 2002).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Most of but not all, R-gene-triggered resistance is accompanied with HR. Insect resistance with HR-like symptoms have also been observed in cases such as wheat (Triticum aestivum) Grover 1995), peach (Prunus persica) resistance to the aphid Myzus persicae (Sauge et al 1998), rice (O. sativa) against the gall midge O. oryzae (Bentur et al 2003), willow (Salix viminalis) tree varieties against the gall midge (Dasineura marginemtorquens; Hoglund et al 2005) and bean (Phaseolus vulgaris) resistance to the bean-pod weevil (Apion godmani; Garza et al 2001). Cell death that occurs during HR+ type resistance is reported to be controlled by the oxidative burst (Atkinson et al 1996;Heath 2000), production of NO (Delledonne et al 2002), and the interaction between some of these different signaling pathways (Delledonne et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…This could also be a case of "extreme resistance mechanism" which is devoid of cell death. It is also noteworthy that resistance conferred by Gm1 gene in the rice variety Kavya is more durable than that conferred by other gall midge-resistant genes which exhibit inducible HR+ type resistance (Bentur et al 2008). Nevertheless, this novel mechanism of resistance needs further characterization.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, studies on inheritance of virulence in biotypes suggested a single recessive gene conferring virulence (Bentur et al 1992). Some of the virulence genes are sex-linked (Behura et al 2000, Bentur et al 2008. Thus a genefor-gene relation was evident between rice R genes and gall midge biotypes (Nair et al 2011), as evident between the Hessian fly biotypes and wheat R genes (Harris et al 2003).…”
Section: The Gene-for-gene Concept and Gall Midge Resistance In Ricementioning
confidence: 93%